Spatial Variability and Secular Changes in Rainfall Influencing Cropping Pattern of Arid Rajasthan - Rao, A S; Purohit, R S (Annals of Arid Zone, 2016)
The monthly, seasonal and annual rainfall (1960-2008) at 65 locations spread in 12 districts of arid Rajasthan were analyzed for identifying spatial variability and shifts in rainfall pattern. Though, the long-term annual rainfall (l901-2009) for the arid Rajasthan showed an increase by 0.15 mm per annum, there was considerable spatial and temporal variability in rainfall at individual locations in the region. The rainfall of June increased at 58 out of 65 locations, whereas, the scenario for subsequent monsoon months was different as it decreased during July, August and September. The rainfall decreased at 36 out of 65 locations in July, 49 in August and 45 in September indicating larger arid area was under reduced rainfall in July, August and September. The seasonal rainfall decreased at 37 locations during monsoon (June to September), 7 in post-monsoon (October and November), 16 in winter (December to February) and 15 during summer (March to May). In the districts having irrigated area 33%, there was no influence on cropping pattern due to the reduction in seasonal rainfall. Key words: Shifts in rainfall, cropping pattern, climate change, Indian arid region.